Seasonal Ecological Stress Assessment of Selorejo Reservoir, Indonesia - Veterina Azahra Firdaus; Yunita Maimunah; Seto Sugianto Prabowo Rahardjo; Wiracha Charoendee; Aulia Rahmawati; Andi Mi'rajusysyakur Muchlis; Andi Nikhlani; Arum Pratiwi (Jurnal Ilmiah Perikanan dan Kelautan, 2026)
Graphical Abstract Highlight Research 1. Selorejo Reservoir shows chronic ecological stress, with instability strongly amplified during the dry season 2. O2 balance remained persistently negative, indicating that TOD frequently exceeded O2 supply. 3. Phosphorus enrichment and P-limited stoichiometry (N:P > 20) promoted eutrophication risk and cyanobacteria dominance. 4. An integrated framework (WQI–nutrients–oxygen–biology) provides a policy-ready basis for seasonally adaptive reservoir aquaculture management.   Abstract Selorejo Reservoir is a multipurpose tropical reservoir increasingly exposed to eutrophication and seasonal oxygen stress, which may undermine ecological stability and limit sustainable aquaculture. To assess the ecological status and quantify its seasonal ecological carrying capacity for aquaculture using integrated nutrient, oxygen, and biological indicators. Seasonal monitoring was conducted from 2022 to 2024 by measuring temperature, pH, DO, BOD, COD, ammonia, nitrite, nitrate, and phosphate. Ecological stress was evaluated using a water quality index (WQI), ecological balance index (EBI), biodegradability index, nutrient stoichiometry, plankton community structure, and phosphorus loading and O2 balance (TOD-based). WQI classified the reservoir as suitable to highly suitable; however, ecological indicators consistently revealed chronic stress. DO frequently approached low levels (4.3–6.7 mg/L) under high organic demand (BOD 5.53–7.48 mg/L; COD 23.08–26.80 mg/L), while phosphate enrichment (0.009–0.422 mg/L) indicated eutrophic to hypereutrophic conditions. N:P ratios were highly variable (10.4–543.3) but mostly >20, suggesting phosphorus-limited yet bloom-prone dynamics. O2 balance remained persistently negative (−2.97 to −6.74 mg/L), EBI was dominated by at risk to exceeded categories, and plankton composition shifted toward strong cyanobacteria dominance in midstream–downstream zones. Selorejo Reservoir has a narrow seasonal ecological tolerance, with the dry season representing the highest-risk period. Sustainable management requires seasonal regulation of cage culture, improved feed efficiency, and watershed phosphorus control; future studies should quantify external nutrient loading and test mitigation scenarios.